PENGARUH KECEPATAN PUTAR PENGADUK DAN WAKTU OPERASI PADA EKSTRAKSI TANNIN DARI MAHKOTA DEWA - Mardina, Primata; Astarina, Eka N.; Aquarista, Septriani (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 2 Juli 2011)
Tannin is one of the chemical compounds which contained in mahkota dewa fruit. The experiment investigated the effects of agitation speed and operation time on percentages of tannin extracted and mass transfer coefficient of tannin extraction process from mahkota dewa. This experiment was conducted in a three neck flask which equipped with mechanical stirrer, condenser, thermometer and heater medium. The sample was heated to 50oC and maintained at that temperature during extraction. The extraction was timed as soon as the mechanical stirrer was turned on. Samples were drawn at specified time interval of 0, 15, 30, 60, 120, 180 and 240 minutes. The result showed that increasing agitation speed and operation time increased the percentage of tannin extracted and mass-transfer coefficient. The highest percentage of tannin extracted was 8,0458% at agitation speed of 700 rpm for 240 minutes and the highest mass-transfer coefficient was 0,03/minute at agitation speed 700 rpm
Keywords: tannin, mahkota dewa, extraction